Tingkat Stres Orang Tua Mendampingi Anak Usia Sekolah Dalam Belajar Daring - Sernovita, Lasmaria; Fadiyah, Dea Putri; Sianturi, Renta; Ramdhania, Desti; Damayanti, Dian; Risdhana, Sillvy; Nurlaela, Siti; Yulianti, Yulianti (Universitas Harapan Bangsa Purwokerto, 2023)
During the Covid-19 pandemic, all schools implemented an online learning model. Therefore, the role of parents is very important during the learning process for school-age children learning online. However, there are some parents who experience stress because the online learning process is not effectively accepted by school-age children, so parents need to re-explain the learning content delivered by the teacher to their children. The purpose of this study was to determine the stress level of parents accompanying school-age children in online learning. The writing method in writing this article is by using a literature analysis of 10 articles with three databases such as Pubmed, ScienceDirect, and Google Scholar. Structured research questions using the PICO method, and keywords based on a combination of Boolean searches (Online OR Online Learning) AND (Pandemic OR Pandemic) AND (Stress OR stress) AND (Parents OR Parents). The inclusion criteria in this article are search techniques using PICO and Boolean, published in Indonesian and English, published in the last 10 years. Results: 10 articles were included in this study. From the results of the critical assessment of the included articles, the average parent experiences stress when accompanying school-age children to learn online. Conclusion: based on 10 articles, it was found that the stress level of parents in accompanying school-age children to learn online is low, moderate and severe stress levels. The majority of parents' stress levels are mild and moderate stress, because parents are getting used to online learning models, with assistance from teachers, whatsapp groups and quota assistance from the government. Some of these efforts are a solution in reducing parental stress